Answer:
One solution
Step-by-step explanation:
5x + y = 8
15x + 15y = 14
Lets solve using substitution, first we need to turn "5x + = 8" into "y = mx + b" or slope - intercept form
So we solve for "y" in the equation "5x + y = 8"
5x + y = 8
Step 1: Subtract 5x from both sides.
5x + y − 5x = 8 − 5x
Step 2: 5x subtracted by 5x cancel out and "8 - 5x" are flipped
y = −5x + 8
Now we can solve using substitution:
We substitute "-5x + 8" into the equation "15x + 15y = 14" for y
So it would look like this:
15x + 15(-5x + 8) = 14
Now we just solve for x
15x + (15)(−5x) + (15)(8) = 14(Distribute)
15x − 75x + 120 = 14
(15x − 75x) + (120) = 14(Combine Like Terms)
−60x + 120 = 14
Step 2: Subtract 120 from both sides.
−60x + 120 − 120 = 14 − 120
−60x = −106
Divide both sides by -60
![\dfrac{ -60x }{ -60 } = \dfrac{ -106 }{ -60 }](https://tex.z-dn.net/?f=%5Cdfrac%7B%20-60x%20%20%7D%7B%20-60%20%20%7D%20%20%20%3D%20%20%20%5Cdfrac%7B%20-106%20%20%7D%7B%20-60%20%20%7D)
Simplify
![x = \dfrac{ 53 }{ 30 }](https://tex.z-dn.net/?f=x%20%3D%20%20%20%5Cdfrac%7B%2053%20%20%7D%7B%2030%20%20%7D)
Now that we know the value of x, we can solve for y in any of the equations, but let's use the equation "y = −5x + 8"
![\mathrm{So\:it\:would\:look\:like\:this:\ y = -5 \left( \dfrac{ 53 }{ 30 } \right) +8}](https://tex.z-dn.net/?f=%5Cmathrm%7BSo%5C%3Ait%5C%3Awould%5C%3Alook%5C%3Alike%5C%3Athis%3A%5C%20y%20%3D%20%20-5%20%5Cleft%28%20%20%5Cdfrac%7B%2053%20%20%7D%7B%2030%20%20%7D%20%20%20%20%5Cright%29%20%20%2B8%7D)
![\mathrm{Now\:lets\:solve\:for\:"y"\:then}](https://tex.z-dn.net/?f=%5Cmathrm%7BNow%5C%3Alets%5C%3Asolve%5C%3Afor%5C%3A%22y%22%5C%3Athen%7D)
![y = -5 \left( \dfrac{ 53 }{ 30 } \right) +8}](https://tex.z-dn.net/?f=y%20%3D%20%20-5%20%5Cleft%28%20%20%5Cdfrac%7B%2053%20%20%7D%7B%2030%20%20%7D%20%20%20%20%5Cright%29%20%20%2B8%7D)
![\mathrm{Express\: -5 \times \dfrac{ 53 }{ 30 }\:as\:a\:single\:fraction}](https://tex.z-dn.net/?f=%5Cmathrm%7BExpress%5C%3A%20-5%20%5Ctimes%20%20%20%5Cdfrac%7B%2053%20%20%7D%7B%2030%20%20%7D%5C%3Aas%5C%3Aa%5C%3Asingle%5C%3Afraction%7D)
![y = \dfrac{ -5 \times 53 }{ 30 } +8](https://tex.z-dn.net/?f=y%20%3D%20%20%20%5Cdfrac%7B%20-5%20%5Ctimes%20%2053%20%20%7D%7B%2030%20%20%7D%20%20%2B8)
![\mathrm{Multiply\:-5 \:and\:53\:to\:get\:-265 }](https://tex.z-dn.net/?f=%5Cmathrm%7BMultiply%5C%3A-5%20%5C%3Aand%5C%3A53%5C%3Ato%5C%3Aget%5C%3A-265%20%7D)
![y = \dfrac{ -265 }{ 30 } +8](https://tex.z-dn.net/?f=y%20%3D%20%20%20%5Cdfrac%7B%20-265%20%20%7D%7B%2030%20%20%7D%20%20%2B8)
![\mathrm{Simplify\: \dfrac{ -265 }{ 30 } \:,by\:dividing\:both\:-265\:and\:30\:by\:5} }](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%5C%3A%20%20%5Cdfrac%7B%20-265%20%20%7D%7B%2030%20%20%7D%20%20%20%20%5C%3A%2Cby%5C%3Adividing%5C%3Aboth%5C%3A-265%5C%3Aand%5C%3A30%5C%3Aby%5C%3A5%7D%20%7D)
![y = \dfrac{ -265 \div 5 }{ 30 \div 5 } +8](https://tex.z-dn.net/?f=y%20%3D%20%20%20%5Cdfrac%7B%20-265%20%5Cdiv%20%205%20%20%7D%7B%2030%20%5Cdiv%20%205%20%20%7D%20%20%2B8)
![\mathrm{Simplify}](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D)
![y = - \dfrac{ 53 }{ 6 } +8](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%5Cdfrac%7B%2053%20%20%7D%7B%206%20%20%7D%20%20%2B8)
![\mathrm{Turn\:8\:into\:a\:fraction\:that\:has\:the\:same\:denominator\:as\: - \dfrac{ 53 }{ 6 }}](https://tex.z-dn.net/?f=%5Cmathrm%7BTurn%5C%3A8%5C%3Ainto%5C%3Aa%5C%3Afraction%5C%3Athat%5C%3Ahas%5C%3Athe%5C%3Asame%5C%3Adenominator%5C%3Aas%5C%3A%20-%20%5Cdfrac%7B%2053%20%20%7D%7B%206%20%20%7D%7D)
![\mathrm{Multiples\:of\:1: \:1,2,3,4,5,6}](https://tex.z-dn.net/?f=%5Cmathrm%7BMultiples%5C%3Aof%5C%3A1%3A%20%5C%3A1%2C2%2C3%2C4%2C5%2C6%7D)
![\mathrm{Multiples\:of\:6: \:6,12,18,24,30,36,42,48}](https://tex.z-dn.net/?f=%5Cmathrm%7BMultiples%5C%3Aof%5C%3A6%3A%20%5C%3A6%2C12%2C18%2C24%2C30%2C36%2C42%2C48%7D)
![\mathrm{Convert\:8\:to\:fraction\:\dfrac{ 48 }{ 6 }}](https://tex.z-dn.net/?f=%5Cmathrm%7BConvert%5C%3A8%5C%3Ato%5C%3Afraction%5C%3A%5Cdfrac%7B%2048%20%20%7D%7B%206%20%20%7D%7D)
![y = - \dfrac{ 53 }{ 6 } + \dfrac{ 48 }{ 6 }](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%5Cdfrac%7B%2053%20%20%7D%7B%206%20%20%7D%20%20%2B%20%5Cdfrac%7B%2048%20%20%7D%7B%206%20%20%7D)
![\mathrm{Since\: - \dfrac{ 53 }{ 6 }\:have\:the\:same\:denominator\:,\:add\:them\:by\:adding\:their\:numerators}](https://tex.z-dn.net/?f=%5Cmathrm%7BSince%5C%3A%20-%20%5Cdfrac%7B%2053%20%20%7D%7B%206%20%20%7D%5C%3Ahave%5C%3Athe%5C%3Asame%5C%3Adenominator%5C%3A%2C%5C%3Aadd%5C%3Athem%5C%3Aby%5C%3Aadding%5C%3Atheir%5C%3Anumerators%7D)
![y = \dfrac{ -53+48 }{ 6 }](https://tex.z-dn.net/?f=y%20%3D%20%20%20%5Cdfrac%7B%20-53%2B48%20%20%7D%7B%206%20%20%7D)
![\mathrm{Add\: -53 \: and\: 48\: to\: get\: -5}](https://tex.z-dn.net/?f=%5Cmathrm%7BAdd%5C%3A%20-53%20%5C%3A%20and%5C%3A%2048%5C%3A%20to%5C%3A%20get%5C%3A%20%20-5%7D)
![y = - \dfrac{ 5 }{ 6 }](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%5Cdfrac%7B%205%20%20%7D%7B%206%20%20%7D)
![\mathrm{The\:solution\:is\:the\:ordered\:pair\:(\dfrac{ 53 }{ 30 }, - \dfrac{ 5 }{ 6 })}](https://tex.z-dn.net/?f=%5Cmathrm%7BThe%5C%3Asolution%5C%3Ais%5C%3Athe%5C%3Aordered%5C%3Apair%5C%3A%28%5Cdfrac%7B%2053%20%20%7D%7B%2030%20%20%7D%2C%20-%20%5Cdfrac%7B%205%20%20%7D%7B%206%20%20%7D%29%7D)
So there is only one solution to the equation.
Answer: the ordered pair negative 3 over 8, negative 5 over 8
Step-by-step explanation:
5 because -2+5=3 explanation
r+2
Explanation:
because if we add 2 to r which is equal to 4 we can get 6